Belawan Maritime Museum (Metaphor Architecture) - Alya Maysarah Daulay; Vinky Rahman (Talenta Publisher, 2023)
Indonesia is a maritime nation with the world's biggest archipelago. Despite the fact that Medan, and particularly the Medan Belawan District, played a significant role in Indonesia's maritime history, the district's potential remains unrealized and has not been utilized and accommodated properly. Media is needed to accommodate and educate the public about the importance of maritime knowledge by providing a museum that can function as a place for preserving maritime history. Unfortunately, the interest of the Indonesian people in visiting museums is still relatively low. Therefore, facilities/facilities and infrastructure are needed to support the function of the museum so that it is more recreational but still informative. The Belawan Maritime Museum is located at K.L.Yosudarso Street, Medan Belawan District, and provides information about Indonesian maritime affairs, especially Belawan. The design approach used is the metaphorical architectural approach. The metaphorical architectural theme with the shape of ships and waves applied to the museum is intended to optimize the appearance and marketability of this building. The use of metaphorical themes is closely related to the visual impression and meaning to be displayed in the building. This building is also expected to become an icon in the area. It is hoped that the design of the Belawan Maritime Museum can further increase the interest and insight of the Indonesian people, especially Medan City, about Indonesian maritime affairs and become one of the attractions of Medan City, especially Medan Belawan District, as a tourist destination for local and foreign tourists.Keywords: Belawan, maritime, metaphor architecture, museum